2022
DOI: 10.1177/21925682221097650
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Predicts Recurrent Lumbar Disc Herniation Following Percutaneous Endoscopic Lumbar Discectomy

Abstract: Study Design Retrospective study. Objectives To develop machine learning (ML) models to predict recurrent lumbar disc herniation (rLDH) following percutaneous endoscopic lumbar discectomy (PELD). Methods We retrospectively analyzed 1159 patients who had undergone single-level PELD for lumbar disc herniation (LDH) between July 2014 to December 2019 at our institution. Various preoperative imaging variables and demographic metrics were brought in analysis. Student’s t test and Chi-squared test were applied for u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…There was no statistically significant difference between two groups. According to the previous studies, higher BMI, Modic changes and history of lumbar surgery were associated with a higher risk of recurrent herniation 21,22 . In our study, a total of 13 patients underwent reoperation.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…There was no statistically significant difference between two groups. According to the previous studies, higher BMI, Modic changes and history of lumbar surgery were associated with a higher risk of recurrent herniation 21,22 . In our study, a total of 13 patients underwent reoperation.…”
Section: Discussionsupporting
confidence: 58%
“…According to the previous studies, higher BMI, Modic changes and history of lumbar surgery were associated with a higher risk of recurrent herniation. 21,22 In our study, a total of 13 patients underwent reoperation. of which four patients (30.8%) were obese (30.8%), six patients (46.2%) had Modic changes in their MRI scans.…”
Section: Complications and Revisionmentioning
confidence: 94%
“…A total of 3 studies ( 23 , 26 , 27 ) reported the association between sacral slope angle and rLDH, and there was heterogeneity among these three studies ( I 2 =86%). Meta-analysis showed that a larger sacral slope angle was a risk factor for rLDH after PELD (WMD=3.48, 95% CI: 0.53 to 6.42), with a statistically significant difference (P=0.02).…”
Section: Resultsmentioning
confidence: 99%
“…Percutaneous endoscopic lumbar discectomy is a commonly used minimally invasive therapeutic strategy for LDH due to its advantages in several aspects such as less soft tissue injury, shorter operation time, and faster recovery. 5 Nonetheless, the incidence of surgery-related complications is 15–30%, and the risk of recurrent LDH after surgery is reported to be 2–25%. 6 Clinically, conservative approaches are frequently employed as the first choice for LDH treatment and have achieved certain favorable outcomes.…”
Section: Introductionmentioning
confidence: 99%